Implementasi Sikadeka untuk Meningkatkan Efektivitas Audit Dana Kampanye Pemilu 2024 pada Partai Politik Kota X - Moh Rifki Alfiansyah; Hero Priono (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This study focuses on the implementation of SIKADEKA in City X during the 2024 Election, evaluating its effectiveness in auditing campaign funds. The research employs a qualitative descriptive method. This type of research aims to report results that reflect the actual conditions related to SIKADEKA in the 2024 campaign fund audit. Data collection methods include document studies and interviews. The objective of this research is to provide a detailed and accurate depiction of the effectiveness of SIKADEKA in campaign fund audits, incorporating various perspectives from stakeholders involved in the 2024 election campaign funds. The results indicate that SIKADEKA is not yet fully effective, as there is still non- compliance in campaign fund reporting and a lack of understanding among political parties about the system, leading to less effective implementation of campaign fund audits using SIKADEKA. The researchers formulate this study to further discuss the implementation of SIKADEKA in enhancing the effectiveness of campaign fund audits in City X.